LEGAL PROTECTION IN MOTORCYCLE PURCHASE TRANSACTIONS THROUGH LEASING ACCORDING TO THE CONCEPT OF MURABAHAH: A Study at PT Mandala Multi-Finance Aceh, Indonesia - Nona Silva Syakina Nuri; Muhammad Yusuf; Riadhus Sholihin (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
This article examines the implementation of consumer rights and responsibilities in motorcycle purchase transactions via leasing at PT Mandala Multi-Finance, focusing on those that apply murabahah contracts. Mandala multi-finance, with a focus on transactions involving murabahah contracts. This research uses a juridical-empirical approach, with primary data obtained through interviews with leasing owners, users, and experts in Islamic economic law. The study results indicate that, when leasing is implemented, there are often cases of default, usually committed by the lessee (the borrower). These defaults can take various forms, such as subleasing, using the goods as collateral for debt, failing to pay late fees, failing to pay due instalments, and delaying lease payments. In some cases, the lessee deliberately misappropriates the goods by selling them. As a result of these breaches of contract, financing companies may suffer losses and have the right to file lawsuits under applicable laws. PT Mandala Multifinance, as a financing institution, must ensure that Islamic standards and relevant regulations are followed in all transactions. The company must draft transparent and balanced contracts and provide consumers with sufficient information regarding their rights and responsibilities. Furthermore, the company must ensure that the vehicle repossession process is carried out by legal procedures, including registering fiduciary guarantees and notifying consumers adequately. By applying the principles of transparency, fairness and compliance with existing regulations, motorcycle leasing at PT Mandala Multi-finance is expected to run smoothly and provide the best legal protection for consumers. Mandala Multifinance will run smoothly and provide consumers with legal protection.